School bullying: victimization in a public primary school in Selangor - Ahmad Sudan, Salmi (2015)
This research paper examines the problem of school bullying in a primary school in the state of Selangor, Malaysia. Particularly the paper looks at bullying victimization with the focus on how bullying affects the thinking, feelings and behavior of the bullying victims. The paper also explores how the school regards school bullying, what type of intervention measures that the school has and how these measures are implemented in the school. Data was collected through in depth interviews with the participants of this study who were two victims of school bullying, a school counselor, and a Discipline Head. The results showed that bullying affects negatively the thinking, feelings and behavior of the victims in which they reported among other feelings of fear, anguish, anger, foolish, and hating school as the outcomes of being bullied. It was also found that the school under study does not have a particular or constant intervention programs for both bullies and victims of school bullying in the school. The implications of these findings for future studies on school bullying-victimization particularly in Malaysia are discussed.